A SHARIA ECONOMIC LAW REVIEW OF CONSUMER BEHAVIOR IN SALES CONTRACTS ON SHOPEE (A CASE STUDY OF STUDENTS AT INSTITUT NIDA EL-ADABI) - Wahdan; Mauludi, Putri Nabila; Syahlarriyadi, Syahlarriyadi; Warmin, Warmin; Widodo, Tri (UTSAHA: Journal of Entrepreneurship, 2025)
Human life is inseparable from economic activities, one of which is buying and selling transactions that are increasingly conducted through e-commerce platforms such as Shopee. This study aims to examine the consumer behavior of students at Institut Nida El-Adabi in Shopee transactions from the perspective of Sharia economic law. A qualitative method is employed to gain an in-depth understanding of the conformity of digital transaction practices with Sharia principles such as honesty (ṣidq), justice (‘adl), and mutual consent (tarāḍī). The findings show that Shopee serves as a primary, practical, and efficient medium for students to fulfill their consumption needs, offering convenience in transaction processes and various payment methods. However, challenges such as product mismatches, delivery delays, and service issues affect consumer satisfaction. Shopee has implemented return and refund mechanisms aligned with the Sharia principle of justice. This study emphasizes the importance of integrating Sharia values into digital business to maintain consumer trust and fairness in transactions, while encouraging service quality improvements in accordance with Islamic economic ethics.